Allergic rhinitis in college students at Dongguan: a cross-sectional survey on disease burden, knowledge, and self-management - Xin Peng; Haiyi Yan; Haixin Feng; Shiqing Huang; Bingsong Zhang; Xueqin Huang; Xueqin Huang (Frontiers in Allergy)
This study examined the prevalence, clinical characteristics, disease knowledge, and quality of life impact of allergic rhinitis (AR) among college students in Dongguan, China. Using a customized questionnaire, we surveyed 1,531 participants (response rate: 85.1%) and identified an AR prevalence of 18.68% (95% CI: 16.72–20.63%). The study identified significant gaps in AR management, including underutilization of allergen testing (only 44.21% of AR patients underwent skin prick testing) and limited medication knowledge among 73% of participants. Environmental control measures were often neglected, and health education was inconsistently delivered, with 72.03% of students relying on the internet for AR information. The findings underscore the need for enhanced health education, improved access to diagnostic testing, and patient-centered communication strategies. Digital platforms and peer-led interventions are recommended to address these gaps and improve AR self-management.